An Integration of Moral Values on the English Text Book of Vocational High School. A Case Study of Critical Discourse Analysis - Sahlan Tampubolon; Usman Sidabutar (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2022)
English Textbook of Vocational High School in terms needs to be assessed for their relevance of the hard skills and soft skills. This research aims to cultivate the integration of moral values found on the ELT textbook of Vocational High School at the grade of X, XI and XII. This research method is a qualitative descriptive research method in the Critical Discourse Analysis of the verbal and visual image. The moral values found on book declares that the respect for other of being friendly occurs in 17.5 %. The book tendency occurs on the social sensitivity which occurs in 7%. Furthermore, the moral value in regarding the students’ hard skill depicts the Creativity with 6.8 %. This indicates that, the fifth sense of Pancasila keadilan social bagi seluruh rakyat Indonesia is clearly found on the book. In addition, the are some meanings implied explicitly on the textbook based on the visual image cultivate the character building in social sensitivity which has an effect to human’s daily life. The study conveys that, the respect for other of being friendly is more emphasized in the ELT textbook. Meanwhile, social creativity in this book is more emphasized with the visual image model. The ELT textbook design of vocational high school provides a lot of very significant insight into students' abilities to learn English as a foreign language the content, topics, use of grammar and methodology reflect moral content, conveying many moral messages such as information about culture, beliefs, and social morals